COMPOSITES OF STARCH ? COUMARIN COMPLEX/MICROCRYSTALLINE CELLULOSE/BIOPOLYMER AS SCENTED PLASTIC MATERIALS - Sita Permatasari, Amaliya
Starch has not been able to fully replace non-biodegradable plastic materials because it has weaknesses, especially related to low mechanical properties. Therefore, to improve the mechanical properties of starch, it is necessary to mix it with other polymers that have a high compatibility with starch. Microcrystalline cellulose (MCC) is a polymer with a high potential to improve the mechanical properties of thermoplastic starch. In addition, the mechanical properties of starch can be enhanced by increasing the crystallinity of starch, including through the formation of complexes between starch and a guest molecule. This study chose coumarin as a guest molecule because it offered additional properties, especially for producing scented plastics. Scented plastics are widely used, in the children's toy industry, aroma therapy packaging, and scented waste plastics. This research consisted of the isolation of cassava starch and its characterizations, the preparation of composite films by the casting method, and the characterizations of the resulting and composite films. The starch ? coumarin complexes blended with microcrystalline cellulose were mixed with other biopolymers, such as poly(vinyl alcohol), xanthan gum, and karaya gum. Optimization in this study included variations in the added biopolymers, the concentration of guest molecules in the complexes, and the amount of plasticizer used. The characterizations of the sample included FTIR, XRD, mechanical test, contact angle, moisture content, microbial biodegradation test, and soil burial test. This study isolated the starch from cassava, yielding 14,05% (w/w). Cassava starch had a water content of 8,03% (w/w) and an amylose content of 19,67% (w/w). Starch ? .? coumarin complexes with 5%, 7%, and 10% (w/w) coumarin content were successfully prepared. Iodine assays showed that within these complexes, the relative percentage of amylose channels not occupied by coumarins ranged from 40 ? 60% for dried samples and 50 ? 70% for non-dried samples. The UV-Vis spectroscopy test of the starch ? .? coumarin complex solution showed a change in absorbance at a